Investigating Environmental Performance Management - Vipin Gupta (Revista Brasileira de Gestão de Negócios - RBGN, 2020)
Purpose: Even though there is a growing recognition of the externality costs of low environmental performance by firms, there continue to be significant inter-firm differentials in environmental performance management. We build on the theories of strategic management to inquire into the factors contributing to these differentials. Design/methodology/approach: Using a 2015 survey sample of Chinese small and medium enterprises, we empirically investigate the alternative thesis that the profit maximization motive constitutes the appropriate heuristic for the performance management of corporate social responsibility factors. Findings: The green capability of a firm is an aggregate of green trading and the investments that the firm has made in green initiatives that are complementary to its strategic business model. The profit aspiration level of firms has a negative influence on their green programing, while transformational leadership has a positive influence. Originality/value: We develop seven propositions represented as algebraic relationships to interpret these factors.